Poverty trend among the lower class households in a rural area of Bangladesh - Kabir, MS; Seamoon, FR; Rahman, MA (Journal of the Bangladesh Agricultural University, 2016)
The study undertakes to determine poverty trend among the lower class households during the last five years in a rural area of Bangladesh. A sample of size 80 lower class households was selected from two villages of Sherpur District in Bangladesh. The finding shows that the yearly average income and expenditure of the households were Tk 30912.50 and Tk. 25925, respectively. The change of the socioeconomic status of the lower class households has played an important role on changing pattern of poverty. Occupation of the respondent was significantly associated with change in poverty situation. A shift from lower level to higher level of a characteristic indicates, as a whole, the community has experienced a positive change in their livelihood. In statistical analysis, binary logistic regression model was fitted best. Among the occupation categories handicrafts seemed to help overcome the poverty situation more than business. Respondents involved in handicrafts were 3.673 times more likely to have a positive change in poverty situation compared to those involved in business. The result further suggests that respondents involved in agriculture were 96% significantly less likely to gain positive change than respondents involved in business and other activities. Findings of the study suggest that government should provide different types of facilities to rural lower class people and increase employment opportunities emphasizing more in handicrafts including handicrafts training. J. Bangladesh Agril. Univ. 12(2): 337-344, December 2014